Reason, metaphysics, and mind new essays on the philosophy of Alvin Plantinga - Plantinga, Alvin; Clark, Kelly James, 1956-; Rea, Michael C. (Michael Cannon), 1968- (New York ; Oxford : Oxford University Press, 2012)
Each of the essays in this volume engages with some particular aspect of philosopher Alvin Plantinga's views on metaphysics epistemology, or philosophy of religion.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Includes index.
Keywords: Plantinga, Alvin